An Ordinance Relating to Misdemeanors, § 42, in The Act of Incorporation and Ordinances of the City of Bunker Hill, Illinois 66 (1873). - (:unkn) unknown (My University, 1873)
§Any person or persons who shall within the limits of said city carry concealed on their persons any knife, bowie knife, pistol, revolver, slung shot, or any other dangerous or deadly weapon for the purpose of unlawfully using the same, shall forfeit and pay the sum of not less than twenty-five dollars."
Keywords: CARRY - INTENT TO COMMIT CRIME